Traditional Food Environment and Factors Affecting Indigenous Food Consumption in Munda Tribal Community of Jharkhand, India - Ghosh-Jerath, Suparna; Kapoor, Ridhima; Barman, Satabdi; Singh, Geetanjali; Singh, Archna; Downs, Shauna; Fanzo, Jessica (Frontiers in Nutrition, 2021)
Indigenous food (IF) systems, derived from natural ecosystems are perceived to be sustainable and nutritionally adequate. Mundas, an indigenous tribal community in Jharkhand India, are surrounded by rich agroforestry resources, yet display high levels of malnutrition. Our study explored the food environment of Munda community , different IFs they accessed, levels of utilization of IFs in routine diets, their nutritional attributes and factors influencing IF consumption. A cross-sectional mixed-methods study was conducted in nine villages of Murhu and Torpa blocks in Khunti district, Jharkhand. Using focus group discussions and key informant interviews, we did free-listing of IFs known to the community. This was followed by enumerating preferred and little used/historically consumed IFs, along with reasons. Qualitative inquiries were recorded and transcribed verbatim; data were coded and analysed using thematic framework approach. The listed IFs were identified through common names and photographs, and verified by ethnobotanist in the team. The nutritive values of identified IFs were searched in literature or nutritional analysis of specific plant based foods were undertaken in an accredited laboratory. The community demonstrated traditional ecological knowledge of several IFs (n=194), which are accessed from wild, cultivated and built food environments. Taxonomic classification was available for 80% (n=156) IFs, out of which 60 foods had nutritive values in secondary literature and 42 foods were analysed in laboratory. Many IFs were rich in micronutrients like calcium, iron, folate, vitamin A and C. Among the listed IFs, only 45% were commonly consumed, while rest were little used/historically consumed. Factors like desirable taste, satiety, perceived nutrition benefits, adaptability to climate variability, traditional practice of food preservation and their cultural importance promoted IF consumption. However, local climate impacts on agroforestry systems, easy access to foods bought from markets or distributed under government food security schemes, and promotion of hybrid seeds by local agricultural organizations, emerged as potential barriers. Thus, reinforcement of traditional ecological knowledge and informal food literacy, along with promotion of climate resilient attributes of IFs, can contribute to sustainable food systems in Munda community.